2008
DOI: 10.1111/j.1365-2702.2007.01985.x
|View full text |Cite
|
Sign up to set email alerts
|

Review: evaluating information systems in nursing

Abstract: The rapid introduction of IT systems for clinical practice urges evaluation of already implemented systems examining how and in what circumstances they work to guide effective further development and implementation of IT systems to enhance clinical practice. Evaluation involves more factors than just involving technologies such as changing attitudes, cultures and healthcare practices. Realistic evaluation could provide configurations of context-mechanism-outcomes that explain the underlying relationships to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 56 publications
(118 reference statements)
2
62
0
1
Order By: Relevance
“…In realistic evaluation, "The main aspect is that of generative mechanisms based on causality being, not external, but an internal potential of the programme or intervention that is activated in the right conditions" [1] (pp 572). Evaluation tries to uncover causal relationships between context, mechanisms and outcomes: what works for whom in what circumstances [10].…”
Section: Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In realistic evaluation, "The main aspect is that of generative mechanisms based on causality being, not external, but an internal potential of the programme or intervention that is activated in the right conditions" [1] (pp 572). Evaluation tries to uncover causal relationships between context, mechanisms and outcomes: what works for whom in what circumstances [10].…”
Section: Design and Methodsmentioning
confidence: 99%
“…Nevertheless, such evaluation can be considered to be in its early stages. Limited insight has been developed and many relevant questions for effective design and implementation remain unanswered [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urquhart et al [41], cited in Oroviogoicoechea et al's review [43], suggested quality of health care is directly related to the quality of information available to healthcare workers thus information management is an essential part of health care delivery. The interviewees' documentation time was perceived to be reduced, allowing staff to spend more time with residents, it is the same as Chau and…”
Section: The Benefits To the Residentsmentioning
confidence: 99%
“…24 Several studies support this perspectives and add new possibilities, such as: improvement of practice environments, direct care, patient results and satisfaction; reduction in the time spent on documentation and clinical record keeping; development and improvement of clinical reasoning skills and judgment; inclusion of nurses in intensive care processes; promotion of clinical discussions among colleagues and the multidisciplinary team; support of the continuous search for information aimed at generating evidence-based care; and guarantee of the continuity of nursing care. 17,19,21,[25][26][27][28][29][30][31][32][33][34] However, in order to provide nurses with the ability to carry out the documentation of rendered care processes, studies point to the need to standardize data entries included in the electronic health record, as well as recover and analyze information by means of a vocabulary that standardizes the clinical terms of the care practice. The standardization of these clinical terms must meet specified criteria such as validity, specificity, data recovery and ease of communication, and must be presented in a way that supports the understanding, knowledge and intuition of the professionals.…”
Section: Health Information and Computing Systems: The Electronic Recmentioning
confidence: 99%